Evaluation of physical and chemical stability of semi-solid preparations towards beyond-use date - Sukamdi, Dyani Primasari; Dewinda, Zulfa Sekar; Damarwati, Vella Lailli; Maziyyah, Nurul; Ningrum, Dhecella Winy Cintya (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2023)
Background: Semi-solid formulations require careful consideration due to potential drug interactions and incompatibilities. The stability of these compounds is crucial for determining the quality of a preparation, often assessed by its designated shelf life. Objective: This research synthesizes previous studies to provide a comprehensive assessment of the quality and stability of semi-solid drugs, focusing on evaluating their physical and chemical stability in relation to the Beyond Use Date (BUD). Methods: A literature review was conducted using the Google Scholar database, yielding eight articles that met the established inclusion and exclusion criteria and were pertinent to the research topic. Results: The evaluations of physical stability indicated that preparations are stable when stored under standard conditions, away from light, and when formulated with suitable bases. The chemical stability assessments revealed a decline in potency or concentration at elevated temperatures. Conclusion: The study concludes that, within the parameters of stability evaluated, semi-solid drug preparations remain viable for use.